2011
DOI: 10.1139/z11-050
|View full text |Cite
|
Sign up to set email alerts
|

A 4-year study of invasive and native spider populations in Maine

Abstract: Invasive spiders pose potential threats to native spiders. In 2002, the European spider Linyphia triangularis (Clerck, 1757) (Araneae: Linyphiidae) was discovered in all but one county in Maine. At Acadia National Park, we conducted a 4-year study of L. triangularis and three native linyphiid species of a similar size ( Frontinella communis (Hentz, 1850), Pityohyphantes subarcticus Chamberlin and Ivie, 1943, and Neriene radiata (Walckenaer, 1842)). Using line-transect surveys, we measured population densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Invasive spiders can negatively impact native arthropod communities in many ways. For example, the presence of invasive Linyphia triangularis led to reduced densities of native spiders (Jakob et al., 2011), increased web abandonment and web building of the native Frontinella communis , and web takeovers of F. communis in Maine, United States (Bednarski et al., 2010). Candy‐striped spiders ( Enoplognatha ovata and E. latimana ) are known to disproportionately prey on pollinators, even actively hunting prey during pre‐dawn periods when insects are typically lethargic (Scott & McCann, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Invasive spiders can negatively impact native arthropod communities in many ways. For example, the presence of invasive Linyphia triangularis led to reduced densities of native spiders (Jakob et al., 2011), increased web abandonment and web building of the native Frontinella communis , and web takeovers of F. communis in Maine, United States (Bednarski et al., 2010). Candy‐striped spiders ( Enoplognatha ovata and E. latimana ) are known to disproportionately prey on pollinators, even actively hunting prey during pre‐dawn periods when insects are typically lethargic (Scott & McCann, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Invasive spiders can negatively impact native arthropod communities in many ways. For example, the presence of invasive Linyphia triangularis led to reduced densities of native spiders (Jakob et al 2011), increased web abandonment and web building of the native Frontinella communis, and web takeovers of F. communis in Maine, U.S. (Bednarski et al 2010). Candy-striped spiders (Enoplognatha ovata and E. latimana) are known to disproportionately prey on pollinators, even actively hunting prey during pre-dawn periods when insects are typically lethargic (Scott and McCann 2023).…”
Section: Impact Of T Clavata On Native Orb Weaving Spidersmentioning
confidence: 99%
“…Trichonephila clavata's large size may facilitate detection, which can aid monitoring its ecological impacts as it spreads, despite the relative recency of invasion. Although invasive spiders have historically received little attention, case studies have demonstrated the ability of certain invasive spider species to compete with, displace, and prey on native spiders (Bednarski et al 2010;Houser et al 2014;Nyffeler et al 1986;Coticchio et al 2023) which can shift spider community composition (Jakob et al 2011). Trichonephila clavata has been observed in locally high abundances, which may limit available web spaces for native orb weavers.…”
mentioning
confidence: 99%
“…In fact, taking orb-weaving spiders as an example, evidences suggest that communities are mainly niche partitioning structured (Shulov and Weissman 1959;Enders 1974;Olive 1980;Brown 1981;Horton and Wise 1983;McReynolds and Polis 1987;Ward and Lubin 1992;Herberstein 1998;Harwood and Obrycki 2005;Richardson and Hanks 2009;Novak et al 2010;Butt and Tahir 2010;Tahir et al 2012;Afzal et al 2013;Michalko and Pekár 2014). Despite the absence of widespread strong interspecific competition evidences in spiders, other authors suggest that this interaction may be considered a determinant factor of spatial distribution patterns, population abundance and species evolution (Spiller 1984 a, b;Nyffeler et al 1986;Polis et al 1989;Hann 1990;Jakob et al 2011;Lewis 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…Seminal studies present contrasting conclusions. Concerning web-building spiders, some suggested that it constitutes an underlying process in the structuration of spider communities (Spiller 1984 a,b;Nyffeler et al, 1986;Polis et al, 1989;Hann, 1990;Jakob et al, 2011;Lewis, 2013;, while others advocate that it is weak or even absent (Wise, 1981;Riechert & Cady, 1983;Horton & Wise, 1983;Wise, 1984;Hoffmaster, 1985;. Putting aside this ambiguity, if the mechanism does commonly occur, it would very likely influence spider growth rates, reproductive output and spatio-temporal distribution.…”
Section: Introductionmentioning
confidence: 99%